The effect of supply chain management on competitive advantage and organizational performance: evident from MSME in food sector - Budi Suprapto; Deonosius Ari Wisnu Wijaya (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study was conducted to determine the effect of supply chain management on competitive advantage and organizational performance. The sample of this study is the owner or manager of micro, small and medium enterprises (MSMEs) in the food industry sector in Magelang Regency. Data was collected by distributing questionnaires directly to 330 respondents. The research framework and hypotheses are tested by using regression analysis. The results of this study indicate that there is an effect of supply chain management on competitive advantage and organizational performance, and there is an effect of competitive advantage on organizational performance. However, the effect of supply chain management on organizational performance shows the effect directly or without intervening variables.